APPLICATION OF MAGNETIC METHODS FOR MONITORING NATURAL AND MAN-MADE PROCESSES ASSOCIATED WITH CRITICAL INFRASTRUCTURE OBJECTS - Menshov, О. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Presented are the results of research studies with the attracting of the GIS and geophysical methods for solving the problems of monitoring of dangerous natural and man-made processes at the areas of the critical infrastructure objects location. The possible ways of the magnetic methods applied for the critical infrastructure objects monitoring were considered. The natural and man-made processes associated with the critical infrastructure were defined. Among them are the objects that can influence the changes in soils, atmospheric air composition, as well as near-surface geological horizons. The most important objects are the energy enterprises, chemical industry, transport network, and landslide areas. The "Rzhyshchev" section and the "Grebeni" site were used as testing objects of the landslide critical infrastructure. According to the results of processing of cosmoimages and measurements of lateral and vertical distributions of magnetic susceptibility of soils and near-surface geological horizons, the classification of territory risks has been carried out. The territory of the cliff on the slopes of the Dnieper is the most potentially dangerous. Anthropogenically impacted natural and man-made territory of the field road and private economy has received an average category of risks. The most risky part of the site are the elements of the landscape, which are located on the land with a minimum slope, the absence of anthropogenic loading, agricultural land and virgin land. Magnetic methods proved to be rapid, effective and low-cost technology for the study of natural and man-made processes associated with objects of critical infrastructure. The integration with other geophysical, soil science methods, and GIS technologies are required.
Keywords: critical infrastructure; natural and man-made processes; soil; environmental magnetism; magnetic susceptibility